2017
DOI: 10.1155/2017/9316506
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Influences of Wellbore Flow on Compressed Air Energy Storage in Aquifers

Abstract: With the blossoming of intermittent energy, compressed air energy storage (CAES) has attracted much attention as a potential largescale energy storage technology. Compared with caverns as storage vessels, compressed air energy storage in aquifers (CAESA) has the advantages of wide availability and lower costs. The wellbore can play an important role as the energy transfer mechanism between the surroundings and the air in CAESA system. In this paper, we investigated the influences of the well screen length on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Well configuration can also affect the performance of a reservoir. Li et al [93] investigated the influences of the well screen length on CAESA system performance using an integrated wellbore-reservoir simulator (T2WELL [94]). Results showed that the well screen length can affect the distribution of the initial gas bubble.…”
Section: Well Configurationmentioning
confidence: 99%
“…Well configuration can also affect the performance of a reservoir. Li et al [93] investigated the influences of the well screen length on CAESA system performance using an integrated wellbore-reservoir simulator (T2WELL [94]). Results showed that the well screen length can affect the distribution of the initial gas bubble.…”
Section: Well Configurationmentioning
confidence: 99%
“…Simulations considering the impact of storage formation depth on operational efficiency found that deeper target formations increased efficiency due to higher storage densities and surrounding working temperatures. 48,49 In general, the density of the working phase will increase with depth (Figure 2) where CO 2 has the highest density in comparison with other potential working phases. In terms of surrounding working temperatures, rock grains in aquifers have a larger specific heat than air, resulting in smaller temperature variations in the system and an anticipated increase in efficiency for storage in porous formations versus salt caverns.…”
Section: ■ Storage Capacitymentioning
confidence: 99%
“…The impact of air confinement on the water infiltration process can be significant for a number of natural conditions [15][16][17]. As reported in Slater and Byers [15], for a finegrained soil underlain by an impervious rock or clay, the rainfall might seal the surface soil and further resist the air escape.…”
Section: Introductionmentioning
confidence: 99%